Biostratigraphic characterization of Lower Jurassic deposits of Georgia by Aminonites. - Topchishvili, M. (Cuadernos de Geología Ibérica, 1998)
The Lower Jurassic deposits playing important role in the geological structure of Georgia are considered here according to structural-facial zones. The characteristic of each zone is accompanied by description of the most typieal ant) paleontologically well-substantiated lithological-stratigraphic units. The paper also argues the problem of interrelation between Lower Jurassic ant) underlying Devonian-Triassic formations. On the ground of Ammonite associations the presence of nearly alí Lower Jurassic stages, several zones of standard scale ant) also regional stratigraphic subdivisions has been recognized.